The effect of COVID-19 on women's experiences of pregnancy, birth and postpartum in Indonesia: a rapid online survey - Linda McGowan; Andari Astuti; Firdaus Hafidz; Cesa Pratiwi; Vinami Yulian; Elizabeth Hughes; Arum Pratiwi; Emi Nurjasmi Indomo; Yu Fu (BMC, 2023)
Abstract Background The interrelationship of psychological and social factors in the current COVID-19 pandemic has been highlighted in research mainly focused on the global north. The impact of lockdowns can exacerbate psychological distress and affect access to services. Less is known about the psychosocial impact on women in the context of lower-middle income countries (LMICs); the aim of this study was to capture the impact of COVID-19 on women's experiences of pregnancy, birth and postpartum in Indonesia. Methods We conducted a rapid cross-sectional online survey of women across all 34 provinces in Indonesia to capture participants' experiences. Data were collected between 10th July to 9th August 2020 including demographics, effects on general and mental health and impact on service use. Descriptive statistics and thematic analysis were used to analyse responses, including those women who self-identified with a pre-existing mental health problem. Results Responses were obtained from 1137 women, this included pregnant women (n = 842) and postpartum women (n = 295). The majority of women (97%) had accessed antenatal care during their pregnancy, but 84% of women reporting feeling fearful and anxious about attending visits, resulting in some women not attending or changing provider. A small number (13%) were denied the presence of a birth companion, with 28% of women reporting that their babies had been removed at birth due to protocols or baby's health. Feeling anxious was a common experience among women (62%) during their pregnancy, birth or postnatal period, with a small number (9%) feeling depressed. Lockdown measures led to tensions within personal and family relationships. Conclusions Women in Indonesia reported that the pandemic added an increased burden in pregnancy, birth and post-partum period: physically, psychologically, spiritually and financially. Maternity services were disrupted and health insurance cover lacked responsiveness, which either directly or indirectly impacted on women's choices, and equal access to care. Given the longevity of the current pandemic there is a need to develop tailored supportive interventions for women and their families and develop bespoke training for midwives and other relevant health professionals.